Osteoma Cutis of the Face in CBCT Images - Daniah Alhazmi; Fatma Badr; Fatima Jadu; Ahmed M. Jan; Zainab Abdulsalam (Hindawi Limited, 2017)
Osteoma cutis (OC) is a rare benign disorder where osseous nodules form in the reticular layer of normal skin. These nodules are formed by the deposition of lamellar bone and are characterized by osteocytes in the core and osteoclasts around the periphery. Interpretation of osteoma cutis cases has always been challenging especially using conventional two-dimensional (2D) radiographs, owing to difficulty in localization. Cone beam CT (CBCT), with its three-dimensional (3D) capabilities, offers a great tool to help detect and diagnose these calcific entities. We report a case of miliary type OC incidentally detected in the maxillofacial region using CBCT imaging.